If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(u+3)=8u-6
We move all terms to the left:
5(u+3)-(8u-6)=0
We multiply parentheses
5u-(8u-6)+15=0
We get rid of parentheses
5u-8u+6+15=0
We add all the numbers together, and all the variables
-3u+21=0
We move all terms containing u to the left, all other terms to the right
-3u=-21
u=-21/-3
u=+7
| -3m=4m+7 | | 8x+7=70 | | 6x^2+14x=2x | | -95=x-8 | | 3(t+8)=15t | | 6y+11=7y+29 | | -18=12x | | x+7=7x-11=2x-6 | | 18=18=−9−3y | | 95=x-13 | | g+7=3 | | 2x+3-5x=15 | | 4x-7+x=-22 | | -8x-9=−6x+5 | | .3-3.6n=4.2* | | 180=(x+12)+100+x | | j/j-1/2=3/4 | | -82=14x | | 16m-21=19-4m | | p+11=44 | | 96-v=281 | | -240+x=9x+70 | | n-5=16n= | | 0.1(x+4)=0.2x-0.1 | | -83=6x | | 0.4(3.6–0.5x)+0.8(1.9+x)= | | 5x-8x=12-5 | | 56/6=nn= | | -14x=51 | | 18y+26=188 | | -8r+2r=114 | | (15+x)+43=x |